2013
DOI: 10.1038/onc.2013.378
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent gene repression through p21 is mediated by recruitment of E2F4 repression complexes

Abstract: The p53 tumor suppressor protein is a major sensor of cellular stresses, and upon stabilization, activates or represses many genes that control cell fate decisions. While the mechanism of p53-mediated transactivation is well established, several mechanisms have been proposed for p53-mediated repression. Here, we demonstrate that the cyclin-dependent kinase inhibitor p21 is both necessary and sufficient for the downregulation of known p53-repression targets, including survivin, CDC25C, and CDC25B in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 69 publications
5
79
0
1
Order By: Relevance
“…A strong candidate for such a factor is the DREAM complex, which represses G 1 /S-expressed cell cycle genes in a p21-dependent manner (26,54). We noticed frequent downregulation of DREAM complex targets in Ki-67-depleted cells, which led us to test whether sensitivity to Ki-67 depletion was also p21 dependent.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A strong candidate for such a factor is the DREAM complex, which represses G 1 /S-expressed cell cycle genes in a p21-dependent manner (26,54). We noticed frequent downregulation of DREAM complex targets in Ki-67-depleted cells, which led us to test whether sensitivity to Ki-67 depletion was also p21 dependent.…”
Section: Discussionmentioning
confidence: 94%
“…As a CDK inhibitor (32,33), p21 blocks CDK-mediated Rb phosphorylation, thereby inhibiting E2F-driven transcription (56). Likewise, it maintains the activity of the transcriptionally repressive DREAM complex, which contains Rb-related p107/p130 "pocket protein" subunits (26,27,54). p21 also directly interacts with PCNA and directly inhibits DNA synthesis (35).…”
Section: Discussionmentioning
confidence: 99%
“…p21 can function as a negative regulator of gene expression, independently of its effects on the cell cycle, through a variety of mechanisms including binding and negative regulation of E2F1 activity, 27,37-39 recruitment of E2F4 repression complexes, 37 and binding and modulation of Estrogen Receptor a -dependent transcription. 40 The impact of increased or decreased p21 activity in stromal fibroblasts remains to be conclusively established, as it has been variously reported that p21 overexpression induces CAF conversion 41 or only cellular senescence without induction of the senescence-associated CAF-related secretory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect p53-mediated gene repression of cell cycle genes whose promoters contain CDE/CHR regulatory motifs occurs through the recruitment of the DREAM repressor complex at their promoters (Benson et al 2014). Interestingly, a recent meta-analysis that combined chromatin immunoprecipitation (ChIP) data with in silico analyses suggested that the human genes CENPA and HJURP are possible DREAM-regulated genes (Fischer et al 2016).…”
Section: Identification Of Functional P53 Regulatory Elements In the mentioning
confidence: 99%